2006
DOI: 10.1111/j.1540-8167.2006.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the Coronary Arteries During Epicardial Radiofrequency Ablation with Intracoronary Chilled Saline Irrigation: Assessment in an In Vitro Model

Abstract: Intracoronary irrigation with chilled saline may protect the coronary artery endothelium from heat-induced damage during epicardial RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Thyer et al demonstrated that intracoronary irrigation with chilled saline in an in vitro ovine heart model protected the CA endothelium from heat-induced damage and reduced the probability of the ablation lesion extending to the CA during epicardial RFA. 43 Follow-up in vivo animal studies and subsequent trials to assess the safety and efficacy of this technique are needed.…”
Section: Prevention Of Coronary Artery Injury From Rfamentioning
confidence: 99%
“…Thyer et al demonstrated that intracoronary irrigation with chilled saline in an in vitro ovine heart model protected the CA endothelium from heat-induced damage and reduced the probability of the ablation lesion extending to the CA during epicardial RFA. 43 Follow-up in vivo animal studies and subsequent trials to assess the safety and efficacy of this technique are needed.…”
Section: Prevention Of Coronary Artery Injury From Rfamentioning
confidence: 99%
“…However, coronary artery injury is an ever present risk (especially near the proximal part of the anterior interventricular vein, see figure) and surgery is still necessary in some cases for VT's originating in this region 15. Cryoablation and potential experimental approaches such as cold saline irrigation are likely to aid these approaches to catheter ablation 11, 16, 17…”
Section: Discussionmentioning
confidence: 99%
“…To confirm lesion boundary delineation, histology was performed on one subset of samples. A bath of nitro blue tetrazolium (NBT), which has been shown to differentiate viable from non-viable myocardial tissue, was prepared (13) . An ablated sample was bisected mid-lesion and incubated at 35 °C for 20 minutes in the NBT bath.…”
Section: Methodsmentioning
confidence: 99%